InSAR from the Socotra Island from June to October 2017 (2017)
In this work, InSAR from the Socotra island using Sentinel 1A data from June to October of 2017 was elaborated using European Space Agency's SNAP. The results revealed that the island experienced general subsidence which is confirmed by the data of a GPS station from the Nevada Geodetic laboratory that also recorded continuous subsidence in the year 2010 in a period of 5 months. Unfortunately, this was the most recent recorded data. Since the island is located between three ridges (Sheba ridge to the north, Gulf of Aden ridge to the north west, and the Carlsbridge rift to the south east), uplift was expected and finding only subsidence was unforeseen. One cause for this subsidence is attributed to the formation of pull apart basins in strike-fault systems en echelon (Burg, 2017) which is supported by the reported presence of normal faults in the northeast of the island (Beydoun & Roy, 1969; Fournier, Huchon, Khanbari, & Leroy, 2007). However, this mechanism only explains the subsidence in the west block; one of the two similar sized blocks that form the whole island according to various studies (Fournier, Huchon, Khanbari, & Leroy, 2007) separated by the Haddiboh transform zone. A probable cause for this subsidence may be the activity of scars from past continental collisions that lie deep in the crust and that control topography (Heron, Pysklywec, & Stephenson, 2016), however with InSAR it is impossible to determine where are these structures and to prove their existence more geophysical surveys are needed to examine the crust's structure there